Nanomedicines targeting the inflammasome as a promising therapeutic approach for cell senescence. (November 2022) - Chaturvedi, Swati; Naseem, Zaiba; El-Khamisy, Sherif F.; Wahajuddin, Muhammad
Abstract: Technological advancements in the present era have enhanced drug discovery and development. Nanomedicines are valuable pharmacotherapeutic tools against several diseases and disorders including aging related disorders. The mechanistic association between nanomedicines and molecular modulation have been investigated by many researchers. Notwithstanding the availability of tremendous amount of data, role of nanomedicines in aging related disorders intending inflammasome transfiguration have not been thoroughly reviewed till now. In the present review, we discuss the application of nanomedicines in aging related disorders. Further, we highlight the recent updates on modulated upstream and downstream signalling molecules of inflammasome cascade due to nanomedicines. The review will benefit researchers targeting nanomedicines as a therapeutic approach towards treatment age related disorders through inflammasome inflection.